Principles of food toxicology - Püssa, Tõnu, 1946- (CRC Press, 2014)
"Following in the tradition of the popular first edition, this book integrates the general principles of toxicology with a systematic characterization of the most important food-borne toxicants. Ideal as a textbook in a Food Toxicology course, this new edition includes a new chapter on food adulterations. Using moderately rigorous biochemistry and chemistry, it also provides expanded coverage of entry and absorption of foreign substances, carcinogenicity, reproductive and developmental toxicology, multi-organ toxicity, flavor enhancers, and nano materials"-- Resumé vydavatele
Terminologický slovník
Keywords: toxikologie potravin; kontaminace potravin; hygiena potravin; food toxicology; food contaminantion; food hygiene; monografie; monographs